Penyuluhan Kesehatan Tentang Pencegahan Tuberkulosis Di Masyarakat Kelurahan Togolobe - Tutik; Maya Sari Soamole; Nia Arfita M Nur; Masra Aslam; Jamaludin Sailili; Nurhadiyat Puradin; Siti Nirwani; Ivon Ariesca (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis whichgenerally attacks the lungs but can also attack other organs of the body. InIndonesia prevalence of tuberculosis cases is increasing every year, one of theprevention efforts that must be carried out is by providing correct information sothat healthy living behaviors can be implemented in everyday life. Objective : toprovide health education about tuberculosis prevention. Method : This serviceactivity is carried out using the lecture and discussion method which is carried outin the Ifad building, Togolobe Village with the target of the general public.Participants attended were 21 people, 8 men and 13 women. Result : there was anincrease in participants' knowledge with an average post-test score higher than thepre-test. Conclusion: there was an increase in knowledge about tuberculosisprevention in the community Togolobe Village